An ultrasonic-based multiphase flow composition meter. (September 2020) - Meribout, Mahmoud; Shehzad, Faisal; Kharoua, Nabil; Khezzar, Lyes
Highlights: Multiphase flow meter using a liquid-gas separator and ultrasonic array sensor. The meter covers 0–95% water-cut and 10–60% GVF. Percentage uncertainty of 2% for water-cut measurement. Percentage uncertainty of 3.5% for GVF measurement. Abstract: Accurate multiphase flow metering using non radio-active sensors is highly required in oil fields. This paper suggests a new concept of multiphase flow metering of flow composition with experimental validation in a large lab-scale multiphase flow loop. The device uses an online flow conditioner which comprises a swirl cage to accelerate the liquid-gas centrifugal forces and generate an annular flow with the liquid phase as outer phase. This recommends the usage of liquid-type clamp-on ultrasonic array probe downstream the separator to measure simultaneously and in real-time both the gas-void fraction (GVF) and the water-cut within the liquid phase. The ultrasonic array features high resonance frequency (i.e. 5 MHz in this paper) and small pitch distance (i.e. 0.5 mm pitch between sensors elements), which helps improving the measurement accuracy. Extensive experiments were conducted using an in-house built multiphase flow loop. The corresponding results indicate that for water-cut ranging from 0 to 95% and GVF ranging from 10 to 60% the meter achieves a maximum percentage error of 2% and 3.5% for water-cut and GVF measurement respectively. Exploring further characteristics of ultrasonic waves such as the amplitude of the received signal can help improving the accuracy even further for higher GVF, which however can't reach 100% since the probe requires a liquid film to operate.